ACCEPTANCE OF E-PERFORMANCE SYSTEMS USING THE TECHNOLOGY ACCEPTANCE MODEL (TAM) APPROACH IN AN OUTSOURCHING COMPANY - Zara Larasati; Imam Ali Yoda; Dr. Ratri Wahyuningtyas (SEAN Institute, 2023)
In the era of technological development, digital-transformation is a widely implemented program in companies. One of the digital transformation applications implemented in the organization is the application of the e-performance jsystem in cleaning services at PT ISS Indonesia. The e-performances system is an Android-based applications system implemented by ISS to monitor the performance of cleaning service employees. The cleaning service carries out this e-performance filling daily to complete previously approved work orders/Service Level Agreements. So this study-aims to examine the acceptance of-the existing e-performance system at PT ISS Indonesia using the-technology acceptance model (TAM) approach. This study aims to determine the effects of perceived usefulness on attitude toward use, the effect of perceived ease of use on attitude toward use, the effect of attitude toward use on behavioral intention to use, and the effect of behavioral intention to use on actual system use e-performance in the TIMAH Energy Resources area. This study used a-questionnaires method by taking a sample of 158 people. This study used-quantitative methods and distributed questionnaires. Data processing uses the PLS (Partial Least Square) analysis-method, and this research method is taken from the basic theory of the Technology Acceptance Model (TAM) and its variables, namely perceived ease of use, perceived-usefulness, attitude toward use, behavioral-intention to use and actual-systems use. This study found that the four research hypotheses were acceptable, and the implementation of the e-performance system at PT ISS Indonesia was well-received in the field. Each variable influences the other to get the results of acceptance of using the e-performance system. Furthermore, it is hoped that the results of this research can be used as material for evaluation and consideration for companies in carrying out digital transformation. In addition, training employees, strengthening the e-performance system, and adding features to the e-performance system can increase the use of this e-performance system.